The role of ginseng derivatives against chemotherapy-induced cardiotoxicity: A systematic review of non-clinical studies - Moini Jazani, Arezoo; Arabzadeh, AmirAhmad; Haghi-Aminjan, Hamed; Nasimi Doost Azgomi, Ramin (Frontiers in Cardiovascular Medicine, 2023)
Aims: Although chemotherapy agents are used to treating cancers, they have serious side effects, like their harmful effects on the cardiovascular system, limiting the clinical use of these chemotherapy agents. This study aimed to systematically investigate the potential role of ginseng derivatives in the prevention of chemotherapy-induced cardiac toxicity. Methods: This systematic review was performed according to PRISMA guidelines strategy in databases till August 2022. First, identify studies related to using search terms in titles and abstracts. After studying and screening 209 articles, 16 articles were selected in this study according to our inclusion and exclusion criteria. Results: According to the findings of this study, ginseng derivatives showed significant changes in biochemical, histological, and heart weight loss, as well as a reduction in mortality, which occurred in the groups treated with chemotherapy agents compared to the control groups. Co-administration of ginseng derivatives with chemotherapy agents inhibited or reversed these changes to near-moderate levels. The protective effects of ginseng derivatives can be due to their anti-inflammatory, anti-oxidant, and anti-apoptotic action. Conclusion: This systematic review shows evidence that concomitant administration of ginseng derivatives improves chemotherapy-induced cardiac toxicity. However, for better conclusions about the practical mechanisms of ginseng derivatives in reducing the cardiac toxic effects of chemotherapy agents and evaluating the efficacy and safety of the compound simultaneously, it is necessary to design comprehensive studies.